Association between Portal Vein Thrombosis and Survival in Non-Liver-Transplant Patients with Liver Cirrhosis: A Systematic Review of the Literature - Xingshun Qi; Junna Dai; Man Yang; Weirong Ren; Jia Jia; Xiaozhong Guo (Gastroenterology Research and Practice)
A systematic review of the literature was performed to analyze the association between portal vein thrombosis (PVT) and survival in non-liver-transplant patients with liver cirrhosis. PubMed, EMBASE, and Cochrane Library databases were searched for all relevant papers which evaluated the prognostic value of PVT in predicting the survival of liver cirrhosis. Meta-analyses were not conducted because the ways of data expression and lengths of follow-up were heterogeneous among studies. Overall, 13 papers were included. The 5-day, 6-week, and 1-year mortality were investigated in 1, 3, and 1 studies, respectively; and all of them were not significantly different between cirrhotic patient with and without PVT. By comparison, the 3-year mortality was reported in 1 study; and it was significantly increased by the presence of PVT. The overall mortality was analyzed in 5 studies; and the association with overall mortality and PVT was significant in 4 studies, but not in another one. However, as for the cirrhotic patients undergoing surgical or interventional shunts, the overall mortality was not significantly associated with the presence of PVT in 4 studies. In conclusion, the presence of PVT might be associated with the long-term mortality in non-liver-transplant patients with liver cirrhosis, but not with the short-term mortality.